Role of small-scale cassava drying plants in improving equitable rural economic growth and development - Best, R.; Henry, Guy (International Center for Tropical Agriculture, 1991)
The identification, introduction and development of cassava drying technology has led to a more stable and wider cassava market in several important cassava growing regions in Latin America. In turn, this has been an incentive for small-scale cassava farmers to increase both cassava area and production using improved cassava production technologies. Farmer cooperatives are managing cassava drying plants where cassava is chipped, sundried on concrete floors, and sold as a low-cost energy substitute to animal feed ration manufacturers. The drying plants need an initial investment of 11,000 US$$ and the average drying floor has an annual capacity of processing 100 ha of cassava in a region where the average farm is 4-6 ha. Local governmental and non-governmental institutions provide support in management and marketing. The first drying project started in Colombia in 1982, and since then, the project has been through 3 phases: (1) pilot phase; (2) semi-commercial phase; and (3) expansion phase. Currently, approximately 51 farmer cooperative managed drying plants are in operation, producing 10,500 ton of dried cassava chips. In addition, some 6,000 ton of chips are being produced and utilized on-farm. The drying technology has spread to Ecuador, Panama, and Brazil, where it has been adopted with great success. Currently it is estimated that some 150-170 drying plants are in operation in Latin America. The cassava drying technology has shown an impact at various levels of beneficiaries and in different forms. Small-scale cassava farmers are the foremost beneficiaries in terms of increased cassava revenues and employment. In addition, improved rural purchasing power increases the demand for urban manufactured goods. Hence, cassava drying technology can improve overall economic growth and development in marginal areas of the tropics.